Integrative Transcriptomics and Proteomics Analyses to Reveal the Developmental Regulation of Metorchis orientalis: A Neglected Trematode With Potential Carcinogenic Implications - Gao, Jun-Feng; Lv, Qing-Bo; Mao, Rui-Feng; Sun, Yun-Yi; Chen, Ying-Yu; Qiu, Yang-Yuan; Chang, Qiao-Cheng; Wang, Chun-Ren (Frontiers in Cellular and Infection Microbiology, 2021)
Metorchis orientalis is a neglected zoonotic parasite of the gallbladder and bile duct of poultry, mammals, and humans. It has been widely reported in Asian, including China, Japanese, and Korea, where it is a potential threat to public health. Despite its significance as an animal and human pathogen, there are few published transcriptomic and proteomics data available. Transcriptome Illumina RNA sequencing and label-free protein quantification were performed to compare the gene and protein expression of adult and metacercariae-stage M. orientalis, resulting in 100,234 unigenes and 3,530 proteins. Of these, 13,823 differentially expressed genes and 1,445 differentially expressed proteins were identified in adult versus metacercariae. In total, 570 genes were differentially expressed consistent with the mRNA and protein level in the adult versus metacercariae stage. Differential gene transcription analyses revealed 34,228 genes to be expressed in both stages, whereas 66,006 genes showed stage-specific expression. Compared with adults, the metacercariae stage was highly transcriptional. GO and KEGG analyses based on transcriptome and proteome revealed numerous up-regulated genes in adult M. orientalis related to microtubule-based processes, microtubule motor activity, and nucleocytoplasmic transport. The up-regulated genes in metacercariae M. orientalis were mainly related to transmembrane receptor protein serine/threonine kinase activity, transmembrane receptor protein serine/threonine kinase signaling pathway. Transcriptome and proteome comparative analyses showed numerous up-regulated genes in adult stage were mainly enriched in actin filament capping, spectrin, and glucose metabolic process, while up-regulated genes in metacercariae stage were mainly related to cilium assembly, cilium movement, and motile cilium. These results highlight changes in protein and gene functions during the development of metacercariae into adults, and provided evidence for the mechanisms involved in morphological and metabolic changes at both the protein and gene levels. Interestingly, many genes had been proved associated with liver fibrosis and carcinogenic factors were identified highly expressed in adult M. orientalis, which suggests that M. orientalis is a neglected trematode with potential carcinogenic implications. These data provide attractive targets for the development of therapeutic or diagnostic interventions for controlling M. orientalis.